The Concept of Food as a Part of the Linguistic Landscape of the World “Based on Uzbek and English Language Materials” (Global Scientific Review, 2023)
The article provides extensive information about the concept of food as a part of the linguistic landscape of the world "on the basis of Uzbek and English language materials".